Технічне обслуговування монотонної системи з урахуванням сумарного напрацювання до відмови кожного її елемента - Peschansky, A. I. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2009)
A semi-Markov model of maintenance for a parallel system has been constructed with allowance of the total failure time of each element. The stationary indexes of the quality of the system functioning have been determined. Optimal values of the failure time of the elements for precautionary maintenance of the system have been found.